Christian churches in Dahomey-Benin : a study of their socio-political role - Claffey, Patrick (Studies on religion in Africa ;, 2007)
This book, divided into two broad sections, examines the state in the Republic of Benin and the socio-political role of the Christian churches. The first looks at the remarkable pre-colonial kingdom of Danxom- and its place in the imagining of the modern contrat social beninois. The second section looks at both the historical role of the mainline churches and the more recent development of a Christianisme beninois. The study concludes that the churches are above all a commentary upon the society in which they find themselves. Rather than an overt challenge to the state, they articulate social distress and the desire for a different future. In times of stress they may prove to be the only viable institutional buttress as well as the arbiter. This study seeks to make a contribution to the understanding of the public role of Christian churches in Africa.